Mesoporous Fe-doped In2O3 nanorods derived from metal organic frameworks for enhanced nitrogen dioxide detection at low temperature. Issue 12 (15th August 2020) - Du, Wenjing; Si, Wenxu; Zhao, Jinbo; Wang, Fenglong; Han, Zejun; Wang, Zhou; Liu, Wei; Lu, Guixia; Liu, Jiurong; Wu, Lili
Abstract: Mesoporous Fe-doped In2 O3 nanorods derived from metal-organic frameworks (In/Fe-MIL-68s) were synthesized for NO2 detection. The morphologies, structures and NO2 gas-sensing performances of the Fe–In2 O3 nanorods were systematically investigated. Texture characterizations demonstrate that the as-prepared Fe–In2 O3 nanorods show rich porous structures, high specific surface areas and reduced grain sizes. Gas-sensing measurements display that the Fe–In2 O3 nanorods derived from In/Fe-MIL-68s with the Fe(Ⅲ) content of 5 mol.% (Fe(5)-In2 O3 ) exhibit high response (82) and short response/recovery time (70/65 s) towards 2 ppm NO2 at 80 °C compared with their counterparts. Besides, superior selectivity and good stability are observed. The sensing mechanism studies reveal that the improved gas-sensing performances are attributed to the decrease in the gran size, the formation of rich oxygen vacancies and band gaps narrowing caused by Fe(Ⅲ) doping. Therefore, this work indicates that the Fe–In2 O3 nanorods derived from metal-organic frameworks precursors can be a promising candidate for NO2 detection.